Analysis of the Influence of the Work Environment and Workload on Job Stress in Employees at Pantai Amal Community Health Center - Anugrah, Muhammad Adryan; Yaniawati, R. Poppy; Veranita, Mira (Asosiasi Ahli Administrasi Indonesia, 2026)
Limited human resources and infrastructure at Pantai Amal Community Health Center in Tarakan trigger occupational stress and task complexity during routine services, health programs, performance evaluations, and accreditation processes. This study aims to analyze the influence of work environment and workload on occupational stress among employees at Pantai Amal Community Health Center in Tarakan City. This study adopted a mixed-methods approach via a cross-sectional design, involving 30 purposively sampled employees from Pantai Amal Puskesmas. Quantitative analysis evaluated work environment and workload effects on job stress, while qualitative insights deepened comprehension of these factors' real-world impacts. Findings confirm both factors significantly influence job stress, consistent with Gibson's theory that stress emerges when demands exceed physical or psychological capacities. Practically, these results guide Puskesmas Pantai Amal management in developing effective workload policies, improving work environments, and fostering supportive conditions to reduce employee stress and enhance well-being.